2019
DOI: 10.14740/jem509w
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Atherogenic Properties of Extra Virgin Olive Oil

Abstract: Extra virgin olive oil (EVOO) is an important constituent of the Mediterranean diet as well as whole grains, vegetables, fruits and nuts. Recent meta-analysis showed that compared to low polyphenol olive oil, high polyphenol EVOO significantly improved measures of malondialdehyde, oxidized low-density lipoprotein (LDL), high-density lipoprotein-cholesterol (HDL-C), inflammatory markers and blood pressure [1], suggesting significant anti-atherogenic effects of EVOO.In a randomized, double-blinded, placebo-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A recent study on 7447 participants concluded that in the group supplemented with Mediterranean diet, containing extra virgin olive oil, was at a lower risk for developing major cardiovascular events compared to the control group (Estruch et al, 2018 ). Many other previous studies have reported that the protective effect of olive oil and its major component oleic acid in cardiovascular disease may derive from its antioxidant (Al‐Shudiefat et al, 2013 ; Fitó et al, 2005 ), antiapoptotic (Chiang & Chao, 2018 ; Elgebaly et al, 2018 ), inotropic (Asoom & Al‐Hariri, 2019 ; Javidanpour et al, 2018 ; Loewi, 1955 ; Pi & Walker, 2000 ), antihypertensive (Alcaide‐Hidalgo et al, 2020 ; Massaro et al, 2020 ), antiatherogenic (Visioli & Galli, 2001 ; Yanai, 2019 ), anti‐inflammatory (Fernandes et al, 2020 ; Santangelo et al, 2018 ), and a reduction in TNF‐α (Papageorgiou et al, 2011 ) effects. However, studies are required to show its use in ameliorating fibrosis and inflammation in later stages of MI.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on 7447 participants concluded that in the group supplemented with Mediterranean diet, containing extra virgin olive oil, was at a lower risk for developing major cardiovascular events compared to the control group (Estruch et al, 2018 ). Many other previous studies have reported that the protective effect of olive oil and its major component oleic acid in cardiovascular disease may derive from its antioxidant (Al‐Shudiefat et al, 2013 ; Fitó et al, 2005 ), antiapoptotic (Chiang & Chao, 2018 ; Elgebaly et al, 2018 ), inotropic (Asoom & Al‐Hariri, 2019 ; Javidanpour et al, 2018 ; Loewi, 1955 ; Pi & Walker, 2000 ), antihypertensive (Alcaide‐Hidalgo et al, 2020 ; Massaro et al, 2020 ), antiatherogenic (Visioli & Galli, 2001 ; Yanai, 2019 ), anti‐inflammatory (Fernandes et al, 2020 ; Santangelo et al, 2018 ), and a reduction in TNF‐α (Papageorgiou et al, 2011 ) effects. However, studies are required to show its use in ameliorating fibrosis and inflammation in later stages of MI.…”
Section: Introductionmentioning
confidence: 99%
“…The olive fruit extract has been known to reduce body weight, diabetes, cholesterol, and inflammation (Ghanbari et al., 2012). Olives contain a wide variety of bioactive components including oleuropein, hydroxytyrosol, and tyrosol that possess health‐promoting properties due to their anti‐allergic (Kishikawa et al., 2017), antioxidant (Khaliq et al., 2015), antiatherogenic (Yanai, 2019), anti‐inflammatory (Maalej et al., 2017), antimutagenic (Issazadeh et al., 2012), and antithrombotic effects (Nasopoulou et al., 2018). Oleuropein is the major bioactive component of unprocessed and un‐ripened green olives which during ripening, due to chemical and enzymatic degradation, is converted to hydroxytyrosol in black olives.…”
Section: Introductionmentioning
confidence: 99%